The influence of the STEM learning model assisted by tinkercad media on elementary school students' critical thinking skills - Alvira Althamiranda; Fitri Nuraeni; Tiara Yogiarni (Yayasan Vifada Cendikia Indonesia, 2026)
This study aims to analyze the effect of the STEM learning model assisted by Tinkercad media on the critical thinking skills of elementary school students and to compare its effectiveness with the Discovery Learning model. A quasi-experimental design with a Nonequivalent Control Group Design was employed. The sample consisted of 40 fifth-grade students from SDN 3 Sindangkasih, divided into experimental and control classes. Data were collected using a validated essay test and analyzed using regression analysis, paired sample t-test, independent t-test, and Mann-Whitney U test. The results showed a significant effect of the STEM model assisted by Tinkercad on students' critical thinking skills, with a contribution of 48.1% (R² = 0.481) and an increase in the average score from 49.16 in the pretest to 63.12 in the posttest. Furthermore, the experimental class outperformed the control class in the posttest (63.12 > 46.66), with a significant difference (p < 0.001). The N-Gain of the experimental class (0.28, moderate) was higher than the control class (0.09, low). The STEM model assisted by Tinkercad is proven effective in improving critical thinking skills and is recommended as an innovative alternative in elementary science and social studies learning, particularly for contextual topics such as natural disasters.